The performance of extracellular polymeric substance (EPS) on stability of Aerobic granular sludge (AGS) - Na, Hamiruddin; Na, Awang; Mg, Shaaban (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Various article which indicating the Aerobic granular sludge (AGS) instability, particularly in prolonged phase operating duration become a significant obstacle to its implementation. Generally, prolonged the operation period will lost its stability that can degrade performance effectiveness.
Keywords: aerobic granular sludge; AGS; extracellular polymeric substance; EPS; stability; osad granulowany; substancja polimerowa; stabilność